The spiritual resistance of Rabbi Leo Baeck psychoanalysis and religion - Marcus, Paul 1953- (Routledge, Taylor & Francis Group, 2025)
"The Spiritual Resistance of Rabbi Leo Baeck provides an overview of the life of Dr. Leo Baeck (1873-1956), a German-Jewish rabbi, theologian, historian and Holocaust survivor, from a psychoanalytic perspective. Paul Marcus approaches Baeck's life and intellectual/theological contribution as it interfaces with a broadly defined psychoanalysis. This book describes and explains how Baeck maintained the rudiments of his autonomy, integration and humanity while remaining in Nazi Germany and while in the ghetto Theresienstadt, displaying astonishing courage, character, and goodness - a triumph of a civilized person amidst Nazi brutality. Marcus also considers psychic resilience and moral psychology and assesses contemporary criticisms of Baeck. The Spiritual Resistance of Rabbi Leo Baeck will be of interest to academics and scholars of psychoanalytic studies, spirituality, Jewish studies and resistance. It will also appeal to psychoanalysts in training and in practice."
Keywords: Baeck, Leo / 1873-1956; Rabbis / Germany / Biography